Chromium yeast improves efficiency and carcass quality of pigs fed ractopamine - Marcolla, Camila Schultz (2017)
This study aimed to evaluate the effects of dietary chromium, CLA, and ractopamine on performance and pork quality of finishing pigs slaughtered at 115 kg BW. Ninety-six crossbred barrows (initial BW= 70.21 ± 1.98 kg) were randomly assigned to 1 of 6 dietary treatments. A diet formulated according to the nutritional requirements of 70- to 100-kg barrows of high lean genotype gaining l.l3 kg/day was used as the control (CON). The other five diets were based on the CON and supplemented as follows: 400 ppb Cr yeast (CrY); 0.5% CLA (CLA); 400 ppb CrY and 0.5% CLA (CrY+CLA); 20 ppm RAC (RAC); 400 ppb CrY and 20 ppm RAC (CrY+RAC). Lysine levels on diets containing RAC were raised by 20% compared to CON. Pigs fed RAC and CrY+RAC were fed CON for the first 17 d, and then the respective diets for the last 28 d on trial. There were 8 replicates per treatment (48 pens; 2 pigs per pen). Means were compared using Tukey test, excluding the CON. Dunnett test was used to compare the means of each diet containing additives to the CON. Initial BW was used as covariate. Pigs fed RAC and CrY+RAC had the highest (P < 001) final BW and ADG. Pigs fed CrY+RAC had higher (P < 001) G:F than pigs fed diets containing additives, except for the RAC. Pigs fed CrY+RAC and RAC had similar G:F, both higher (P < 001) than pigs fed CON. Feed intake was similar (P = 0.89) for all diets. Pigs fed CrY+RAC had higher LM area (P 005) and carcass yield (P < 001) than pigs fed CON, CrY, CLA, and CrY+CLA. Loin muscle area and carcass yield of pigs fed RAC were not statistically different from pigs fed the others diets tested. Back fat depth was lower (P = 022) in pigs fed CLA, RAC and CrY+RAC compared to pigs fed CON. The additives did not affect pork pH (P > 005), temperature (P > 005), water losses (P = 0.87), and shear force (P = 0.70). Lower L* values were found on pork from pigs fed CrY+CLA compared to pigs fed CON (P < 005), and RAC (P < 0.01). Pigs fed the RAC had lower (P 005) a* values compared to pigs fed CON. Pork b* values were similar (P = 0.20) for all diets. There were no significant differences (P = 089) on intramuscular fat content. Serum urea nitrogen (SUN) concentration was lower (P = 003) in pigs fed CrY+RAC than in pigs fed CON and RAC. In summary, when combined, CrY and RAC increase LM area and carcass yield and reduce SUN, suggesting a synergism that might be related to the ability of Chromium to improve nutrient utilization in RAC-fed pigs. Additionally, CrY, CLA and RAC have no major effects on pork quality.